Early respiratory experience and subsequent cough and peak expiratory flow rate in 36 year old men and women. Issue 6583 (23rd May 1987) - Britten, N; Davies, J M; Colley, J R
Abstract : Earlier work on the respiratory health of members of the Medical Research Council's national survey of health and development (1946 birth cohort) was extended to age 36. At that age measures of peak expiratory flow rate and respiratory symptoms, elicited by the MRC chronic bronchitis questionnaire, were made in 3261 cohort members. In both men and women lower peak expiratory flow and higher respiratory morbidity were independently associated not only with current indices of poor social circumstances and cigarette smoking but also with poor home environment at age 2 years and lower respiratory tract illness before age 10. The findings provide additional evidence for a causal relation between childhood respiratory experience and adult respiratory disease.